Modelling school principals’ soft skills with sustainable administrative effectiveness - Awodiji, Omotayo Adewale; Katjiteo, Ancia (International Journal of Evaluation and Research in Education (IJERE), 2024)
Effective school leadership is pivotal to the success of educational institutions. While traditional leadership models have emphasized technical skills and administrative competencies, the significance of soft skills in educational leadership has gained increasing attention in recent years. This study explores the direct and indirect relationship between principals’ soft skills and sustainable administrative effectiveness (SAE). The objectives that guided this study are to investigate the direct and indirect influence of soft skills (critical thinking, empathy, communication, adaptability, and leadership) on the SAE of school principals. Stratified and random sampling techniques were adopted to select the participants. Questionnaires, school principals’ soft skills questionnaire (SPSSQ) and sustainable administrative effectiveness questionnaire (SAEQ), were administered to about 432 teachers. The findings revealed a strong positive correlation between principals’ soft skills and their SAE. Therefore, all soft skills directly relate to SAE except critical thinking skills. Empathy, communication, adaptation and innovation, and leadership skills were found to have direct effect on SAE. Whereas critical thinking has no direct effect on SAE but could influence indirectly SAE through other factors. This ultimately results in the achievement of SAE with indirect relationships. Based on the research outcomes, this study suggests that school administrators should invest in professional development programs to enhance principals’ soft skills to achieve SAE.